1995
DOI: 10.1152/ajpheart.1995.269.5.h1735
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of pacemaker activity of sinoatrial node cells by electrical load imposed by an atrial cell model

Abstract: To investigate the electrotonic modulation of sinoatrial (SA) node pacemaker activity by atrial muscle, single or multiple (2-7) SA node cells isolated from rabbit hearts were connected to a membrane model [resistance-capacitance (R-C) circuit] of an atrial cell through an external circuit that mimics the gap junctional conductance (Gc) between cells. When Gc was 0 nS (uncoupled conditions), all the preparations generated regular and stable spontaneous action potentials with a mean cycle length (SCL) of 263 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…In the second case, in a computer simulation study, coupling of an atrial cell to a sino-atrial node cell again slowed the pacemaker activity of the sinoatrial node cell (Boyett, Holden, Zhang, Kodama & Suzuki, 1995a). Both studies suggest that activation of K,ACh in the atrial muscle will slow the pacemaker activity of the sinoatrial node: in the study of Watanabe et al (1995), an increase in the conductance of the analogue atrial cell model slowed the pacemaker activity of the sino-atrial cell, and, in the simulation study of Boyett et al (1995a), the activation of iK,ACh in the atrial cell slowed the pacemaker activity of the sino-atrial node cell coupled to it. Although these studies support the concept of control of the sino-atrial node by atrial muscle, the geometry of the sino-atrial node is complex (ten Velde et al 1995) and further study needs to be carried out with a more realistic model of the sino-atrial node.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the second case, in a computer simulation study, coupling of an atrial cell to a sino-atrial node cell again slowed the pacemaker activity of the sinoatrial node cell (Boyett, Holden, Zhang, Kodama & Suzuki, 1995a). Both studies suggest that activation of K,ACh in the atrial muscle will slow the pacemaker activity of the sinoatrial node: in the study of Watanabe et al (1995), an increase in the conductance of the analogue atrial cell model slowed the pacemaker activity of the sino-atrial cell, and, in the simulation study of Boyett et al (1995a), the activation of iK,ACh in the atrial cell slowed the pacemaker activity of the sino-atrial node cell coupled to it. Although these studies support the concept of control of the sino-atrial node by atrial muscle, the geometry of the sino-atrial node is complex (ten Velde et al 1995) and further study needs to be carried out with a more realistic model of the sino-atrial node.…”
Section: Discussionmentioning
confidence: 95%
“…In terms of function, structure and properties the sino-atrial node is not a homogeneous structure: the centre of the sinoatrial node normally serves as the leading pacemaker site, whereas the function of the periphery of the sino-atrial node is to conduct the action potential from the centre to the surrounding atrial muscle (Bleeker, Mackaay, Masson-Pevet, Bouman & Becker, 1980). The cells in the centre are smaller than those in the periphery and contain fewer myofilaments (Oosthoek, Viragh, Mayen, van Kempen, Lamers & Moorman, 1993); the electrophysiological properties of the tissue vary in a graded fashion from the centre to the periphery (Kodama & Boyett, 1985), perhaps as a result of a regional variation in the density of membrane currents (Oei, Van Ginneken, Jongsma & Bouman, 1989;Honjo & Boyett, 1992;Honjo, Boyett & Kodama, 1995;Nikmaram, Boyett, Kodama & Suzuki, 1995;Nikmaram, Kodama, Boyett, Suzuki & Honjo, 1996). As a consequence of the regional variations in the electrophysiological properties of sino-atrial node tissue, the responses to interventions (e.g.…”
mentioning
confidence: 99%
“…Furthermore, in a simulation study, Boyett et al (1995b) showed that ACh can theoretically slow the spontaneous activity of the SA node by this indirect route. In another study in which an SA node cell was coupled to a passive model of an atrial cell, increasing the conductance of the model atrial cell to mimic the activation of the muscarinic K ϩ channel by ACh led to a decrease in the spontaneous rate of the SA node cell (Watanabe et al 1995).…”
Section: Abundance Of Kir31 and Kir34 Proteins In Sa Nodementioning
confidence: 99%
“…The coupling clamp has been used to study e.g. electrotonic modulation of the pacemaker activity of the sinoatrial node by the atrial muscle (Watanabe et al 1995), or the interaction between Purkinje cells and ventricular cardiomyocytes (Huelsing et al 1998). In some of these studies (e.g.…”
Section: Ap Clampmentioning
confidence: 99%
“…In some of these studies (e.g. Watanabe et al 1995), one of the cells is replaced by a model of cardiomyocyte.…”
Section: Ap Clampmentioning
confidence: 99%